ИНСТИТУТ СЛУЖЕБНОЙ ТАЙНЫ В РЕСПУБЛИКЕ КАЗАХСТАН (Journal of actual problems of jurisprudence, 2019)
In the article of the masters degree candidate are considered concept and protection of the official secret which draws to itselfspecial attention not only from outside of the state but also a society as a whole, in the light of the numerous actions of proceedingconnected with disclosure of the official secret. The questions connected with the official secret, its protection, and also questions ofdisclosure of the official secret were and remain actual at all times.